Proposição de um framework para a implementação do processo de logística reversa para veículos em final de vida no Brasil - Franzini Filho, Carlos Roberto (2015)
Currently in Brazil and the worldwide, the "end of life vehicles" (ELV) has been considered as a serious problem to environment. It is considered as an ELV the vehicle that concluded his life cycle or vehicle damaged due accidents. Unlike countries where recovery ELV happens because of specific ELV laws, recovery of ELV parts in Brazil has been guided by profit in reason of the possibility to reselling parts with highest market value after the first phase of use. The aim of this study was to identify what are necessary steps to propose a framework to implementation of reverse logistics process to ELVs in Brazil. The methodology used to achieve the aim was a theoretical / conceptual research from bibliometric review of the literature available in five databases (CAPES, EBSCO, PROQUEST, SCIENCE DIRECT, GOOGLE ACADÊMICO) and documentary research in Unions and class Associations. A content analysis from collected data allowed the identification of the main aspects and activities related to reverse logistics to ELV. Considering the current scenario for ELVs in Brazil and the data obtained from the literature during the content analysis, a framework was proposed with the required steps to implement the reverse logistics to ELV in Brazil. In reason of a theoretical study, there are limitations because of the different realities from researched countries: changing regulatory, social structures, political systems, laws, economic systems and also the level of development from the country.